2019
DOI: 10.3892/ol.2019.10058
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of temperature changes in photothermal therapy induced by combined application of indocyanine green and laser

Abstract: Photothermal therapy, a type of laser application, has the ability to eradicate tumor cells by a local thermal effect and elicit a tumor specific immune response. Indocyanine green (ICG), a photosensitizer, can effectively elevate the local temperature by absorbing energy from the laser. The present study aimed to investigate the characteristics of temperature changes during photothermal therapy with an infrared thermometer in an ICG solution and in tumor-bearing mice treated with a combination of laser and IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…We have demonstrated that the hmFRT can detect BBR emitted from a tissue at temperatures down to 35°C using a 2 m silica fiber as the transmission media. After calibration, the hmFRT can accurately track tissue temperature change at a rate of 10°C/minute, which is a response time comparable to other studies for hyperthermia treatment . Such sensitivity and tracking ability show that hmFRT is promising for detecting two important hyperthermia temperature ranges, 40 to 45°C and 50 to 80°C, during thermotherapy.…”
Section: Discussionmentioning
confidence: 65%
“…We have demonstrated that the hmFRT can detect BBR emitted from a tissue at temperatures down to 35°C using a 2 m silica fiber as the transmission media. After calibration, the hmFRT can accurately track tissue temperature change at a rate of 10°C/minute, which is a response time comparable to other studies for hyperthermia treatment . Such sensitivity and tracking ability show that hmFRT is promising for detecting two important hyperthermia temperature ranges, 40 to 45°C and 50 to 80°C, during thermotherapy.…”
Section: Discussionmentioning
confidence: 65%
“…However, the maximum temperatures were not the same, and according to the concentration from high to low, the temperatures were 45.0, 42.8, 39.0, 36.8 °C (Figure b 1 ). Many studies have confirmed that the key to hyperthermia is temperature control, and 40–45 °C is the proper temperature for killing tumors, while the normal tissues are not or minimally damaged . In this study, the two higher-concentration groups (15 and 20 mg/mL) quickly obtained the required temperature after laser irradiation.…”
Section: Results and Discussionmentioning
confidence: 50%
“…After irradiation with a near-infrared (NIR) laser, ICG can complete photothermal energy transfer to readily increase the local environmental temperature to above 10 C within minutes. 24,25 In this case, the degradation of SpyCas9 was achieved by co-incubating VPA with ICG after NIR irradiation for 180 s, while the reduction could not be confirmed at a single treatment with other VPA or ICG (Figure 3A; Figure S3A). Interestingly, warming with an external heat bag resulted in a mild reduction of SpyCas9 (Figure 3B; Figure S3B).…”
Section: Vpa Destabilizes Spycas9 Protein In Cellsmentioning
confidence: 90%